IMPLEMENTASI MODEL MENGHAFAL QUANTUM TAHFIDZ AL-QUR’AN DALAM MEMPERMUDAH HAFALAN SANTRI PONDOK PESANTREN TAHFIDZUL QUR’AN AL-ASY’ARIYYAH 6 KALIERANG SELOMERTO WONOSOBO - Nafiah, Aghisna Rizkia; Mukromin, Mukromin; Rois, Ahmad (FAKULTAS ILMU TARBIYAH DAN KEGURUAN UNIVERSITAS SAINS AL-QUR'AN, 2019)
Quantum tahfidz of the Qur'an includes specific instructions for creating an effective environment for memorizing the Qur'an, designing curriculum, conveying content and facilitating the memorization process. That memorizing the Quran is not easy to do. Not everyone is able to do it. due to inappropriate strategies and methods, the results are also unsatisfactory. Then came the model of memorizing the Quantum Tahfidz Al-Quran at Pondok Pesantren Al-Asyariyyah 6 Kalierang which is a model for memorizing subordinates from the central Al-Asyariyyah boarding school. The research conducted is descriptive-based research describing a process that occurs in the field of qualitative research.The sources of data used in this study came from the caregivers of the Al-Asyariyyah 6 boarding school, the supervisors, administrators, and Al-Asyariyyah 6 tahfidz students. Data collection was done by interviewing observations, documentation. After the data is collected then the data is analyzed by data reduction, data presentation, and conclusion drawing. The results of the research conducted by the authors show that 1) the Quantum Tahfidz Al-Quran memorization model makes it easier for students to memorize the Koran, students do not mind, increase the enthusiasm of students in advancing the tahfidz program that is developing, it becomes the interest of students in memorizing the Koran, especially for children who memorize while at school. 2) The implementation of the QTA memorization model that has been implemented in Pondok Al-Asyariyyah 6 is quite effective, it can make students memorize faster, increase fluency in the Koran, and can recite well. 3) One of the supporting factors is that children are happy in applying the QTA memorization model in memorizing so that it is not always monotonous. While the inhibiting factor is the lack of high creativity in children in making symbols or formulas in memorizing